2021
DOI: 10.1177/15589250211022331
|View full text |Cite
|
Sign up to set email alerts
|

Cost optimization of sodium hypochlorite bleaching washing for denim by combining ensemble of surrogates with particle swarm optimization

Abstract: Sodium hypochlorite bleaching washing process has been broadly carried out in denim garment industrial production. However, the quantitative relationships between process variables and bleaching performances have not been illustrated explicitly. Hence, it is impractical to determine values of the variables that can achieve the optimal production cost while satisfying the requirements of customers. This paper proposes an optimization methodology by combining ensemble of surrogates (ESs) with particle swarm opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The emerging of digital twin in the industrial domain provides feasible solution ideas [24][25][26]. As aforementioned, although a large number of scholars have conducted modeling studies on digital twins and achieved some results in related fields [27][28][29], it remains empty of a robotic general digital twin frameworks for the chemical industry, especially for the papermaking industry. Therefore, this paper proposes a digital twin-based data visualization model based on CADSIM Plus simulation software for the papermaking industry to promote the process performance.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging of digital twin in the industrial domain provides feasible solution ideas [24][25][26]. As aforementioned, although a large number of scholars have conducted modeling studies on digital twins and achieved some results in related fields [27][28][29], it remains empty of a robotic general digital twin frameworks for the chemical industry, especially for the papermaking industry. Therefore, this paper proposes a digital twin-based data visualization model based on CADSIM Plus simulation software for the papermaking industry to promote the process performance.…”
Section: Introductionmentioning
confidence: 99%
“…14 It was concluded that the neural network method can provide more accurate predictions than the linear regression method. Xu et al 15 used a combination of surrogate ensemble and particle swarm optimization to optimize the quantitative relationship between the denim bleaching performance of sodium hypochlorite bleached denim and its process variables. Similarly, they have also attempted to optimize the production cost of enzyme washing of indigo dyed cotton denim by combining kriging surrogate with a differential evolution algorithm.…”
mentioning
confidence: 99%